Green Knowledge Sharing for Sustainable Competitive Advantage in The Halal Industry Through an HRM Perspective - Rahmat, Taufiq; Ahman, Eeng (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
Research aim: This research aims to explore the role of Green Human Resource Management (GHRM), Green Knowledge Sharing (GKS), green leadership, and employee green behavior in achieving sustainable competitive advantage (SCA) in the halal industry, using the Resource-Based View (RBV) perspective. Method: This study uses a systematic literature review (SLR) to analyze the relationship between GHRM, GKS, green leadership, and employee green behavior towards SCA. Data were collected through a thorough search in Scopus and Google Scholar databases with related keywords. Research Findings: Findings show that GHRM, GKS, and green leadership play important roles in improving SCA. GHRM and GKS strengthen employee green behavior, which supports the organization's environmental performance. Green leadership improves the implementation of GHRM and GKS and strengthens the relationship between GHRM and employee green behavior. Employee green behavior also acts as a mediator between GHRM and SCA. Theoretical Contribution: This research expands the understanding of how green HRM practices and knowledge sharing contribute to sustainable competitive advantage, especially in the halal industry, which must comply with Sharia principles and global environmental standards. Practical Implications: These findings provide practical guidance for the halal industry in Indonesia to integrate GHRM and GKS with Sharia principles and implement green leadership to achieve sustainable competitive advantage in the global market. Research Limitations: This research is limited to the literature available in the database and may not cover all practical and theoretical aspects of GHRM and GKS in the halal industry.